Using cloud services in distance learning course - I. V. Gerasimenko; V. V. Glyshenko (Academy of Cognitive and Natural Sciences, 2015)
The aims of the research is the presentation of the main approaches to the use of the cloud service in distance learning course. The objective of the exploring is the analysis of the various cloud technologies for learning process. The object of the research is the learning process of students using a cloud services. The study is the usage method is the use of cloud services in education. Results can be used to deliver cloud services in the educational process of most schools.